1954
DOI: 10.1161/01.cir.9.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Commissurotomy for Rheumatic Aortic Stenosis

Abstract: As long ago as the middle of 1949 it had been demonstrated by the senior author that any blunt dilating mechanism applied within the stenotic aortic orifice would, upon expansion, force the separation of one or more of the fused commissures. Thus the diminutive valve orifice could be enlarged without the creation of additional insufficiency and with the restoration of such part of the original valve function as the pathologic distortion of the leaflets would permit. In other words the principles and effectiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0
2

Year Published

1955
1955
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(6 citation statements)
references
References 7 publications
1
3
0
2
Order By: Relevance
“…Kiloh (1950) concluded that a congenital bicuspid valve may well play an important role in the development of calcific aortic stenosis. A similar conclusion is reached by Bailey et al (1954).…”
Section: Smith and Ma Tthewssupporting
confidence: 83%
“…Kiloh (1950) concluded that a congenital bicuspid valve may well play an important role in the development of calcific aortic stenosis. A similar conclusion is reached by Bailey et al (1954).…”
Section: Smith and Ma Tthewssupporting
confidence: 83%
“…Die große Operations-Mor talität stellt die größte Schwierigkeit dar. Sie beträgt ungefähr 20%; sie ist etwas niedriger hei der transaortalen und etwas höher hei der transventrikulären Methode (1)(2)(3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Einleitung Die Entscheidung Ob Einem Patienten Mit Isolunclassified
“…3 6 Schweizer, ü b e r die Häufigkeit Dieses Ergebnis bestätigt dasjenige einer Anzahl früherer Unter suchungen (19,24,27). Es steht jedoch im Widerspruch zu ande ren (7,20,22,23,28 (1,3,7,9,18,27), kann viel leicht auch durch den Altersunterschied der Operierten erklärt werden. Bei begleitender Mitralstenose wird der Kranke den Arzt früher aufsuchen und damit vielleicht früher zur Operation ge langen.…”
unclassified
“…This accomplishment inspired the development of different techniques of aortic valvotomy in the fifties [7][8][9][10] , with varying degrees of both success and complication, including valvar insufficiency.…”
mentioning
confidence: 99%